Economic Performance of Small Ruminants on Smallholder Farms in Climate Smart Villages of Nyando - Sila, Winfred; Gachuiri, Charles Karuku; Recha, John W.M.; Audho, James O.; Ojango, Julie M.K. (2019)
Small ruminant production forms an integral part of the livelihoods of smallholder farmers in Nyando. This paper is part of a study to evaluate the impacts of the small ruminants on the incomes of smallholder farmers adopting “Climate Smart” agricultural practices in the counties of Kericho and Kisumu in Nyando. A cross-sectional survey involving 162 households was conducted in 2018 to elicit information on farmer demographic characteristics, resource endowment, flock dynamics, and revenues from small ruminant production. Results from the analyses of the data collated showed that the small ruminants are an important source of revenue for the smallholder farmers. The number of animals owned varied depending on the size of the land owned. Farmers in Kericho tended to have larger land holdings than in Kisumu (p<0.01) with concurrently larger flock sizes. The farmers however did not have any information on the optimal number of animals that they should keep on their land. In both counties, better prices were received for larger mature animals than for immature animals. The farmers also tended to sell more female than male animals although they stated that the sale of animals was dependent on the availability of the animals and the anticipated returns. Information on the optimal number of animals to rear with specific resources available is needed for the farmers to be able to continually produce and market sheep and goats at a good price.